Аспекти, які впливають на конкурентоспроможність фізкультурно-спортивної організації - Liudmyla Shuba; Victoria Shuba; Victor Shuba (Lesya Ukrainka Volyn National University, 2021)
The current life requires the well-coordinated work and skills to respond the changes in various fields of life. Especially those that influence the maintenance of a healthy human life. The Purpose of the Study is to analyze the competitiveness of sports organization on the base of relevant indicators study in order to manage the sports enterprise competitiveness level. Research Organization. The study was performed since October 1, 2019 to July 1, 2020, in the physical culture and sports organization - Sports Club Sportexpert. The analysis of the services competitiveness was carried out through the example of the sports enterprise - Sports Club Sportexpert. SWOT analysis has been widely used in the process of strategic planning, which divides factors and phenomena into four categories: strengths and weaknesses of the project; opportunities that open up during its implementation and threats associated with its implementation. Results of the Research. The obtained results are aimed at assessing the competitiveness level of the Sports Club Sportexpert. They necessitated the development of certain measures for influence specific competitive indicators. Therefore, it was proposed to expand the discount system - to include discounts for certain age groups, as well as formed discounts on the purchase of sports nutrition, while paying an annual pass. Also, it was suggested to hold a number of activities with a purpose of the sports club promotion. It is proposed to update partially the training equipment in order to influence its quality. Conclusion. The competitiveness level of any enterprise is an important factor influencing the efficiency and success of its activities.